A bibliometric analysis of the research on language attitudes towards English accents - Li, Shengnan; Ting, Su Hie (Higher Education and Oriental Studies, 2021)
A bibliometric analysis was undertaken to chart the development of publications on language attitudes towards English accents in SCOPUS-indexed journals. Publication data were collected from SCOPUS for 1974–2021, and by-hand pre-processing of the data was undertaken to identify reviews and original research articles. VOSviewer was used to create bibliometric networks from 468 articles. The United States published the most articles on language attitudes towards English accents (119, 25.4%), followed by the United Kingdom (54, 11.5%) Australia (35, 7.5%), and Hong Kong (24, 5.13%). In comparison, few have studied the attitudes of non-native English speakers towards English varieties and accents in the Asian region. Although China has the largest English-speaking population in the world, citation numbers for publications on attitude towards English accent in China is low. However, the visualisation of time map on countries/regions of publications identifies China, South Korea, Malaysia, Indonesia, Iran, Thailand, and Turkey as emerging regions where research on attitudes towards English accent is growing. Analysis of publication sources showed that Journal of Multilingual and Multicultural Development, World Englishes and Asian Englishes were the most frequent publishers of articles on attitudes towards English accents. The mapping revealed that the top five authors publishing on attitudes towards English accent are from inner-circle countries, particularly, the United States and the United Kingdom. In terms of research area, the bibliometric analysis revealed a concomitant shift from interest in native speaker perceptions to non-native speaker perceptions of comprehensibility of different English varieties and self-identity consciousness of English language learners.